Multifocal Tuberculosis Verrucosa Cutis: Case Report and Review of the Literature - Niki Ntavari; Vasiliki Syrmou; Konstantinos Tourlakopoulos; Foteini Malli; Irini Gerogianni; Angeliki-Viktoria Roussaki; Efterpi Zafiriou; Maria Ioannou; Eirini Tziastoudi; Konstantinos I. Gourgoulianis; Ioannis Pantazopoulos (Medicina, 2023)
Cutaneous tuberculosis (TB) is still a major public health problem worldwide. Tuberculosis verrucosa cutis (TBVC) is a cutaneous form of exogenous TB caused by exogenous reinfection in previously sensitized individuals. TBVC typically presents as a unifocal condition. Multifocal cutaneous lesions without any other tubercular foci are extremely rare in exogenous TB and few cases are reported in the literature. We describe the first case of multifocal TBVC in an 81-year-old Greek man. In total, 14 cases of multifocal TBVC have been reported in the literature (8 males and 6 females), with mean age 47.64 years (SD = 20.75) and mean time to diagnosis of 9.69 years (SD = 15.31). Most cases (11/12) responded rapidly to treatment, implying the accuracy of diagnosis, while no one was reported to be immunocompromised. Finally, in 10 cases (71.4%), history of skin microtrauma was reported (related either to daily life habits or to professional praxis), confirming it as the main risk factor. The tuberculin skin test was positive in 10 cases and tissue culture for mycobacteria was negative in all cases. TBVC can present with multiple lesions, even in countries where TB prevalence is not high, especially in patients with history of skin abrasions. Prompt specialist assessment can expedite the establishment of diagnosis.